TERAPI PADA PSORIASIS - Febriyani Dyah Kusuma Dewi (Yayasan Pendidikan Medika Indonesia, 2021)
Psoriasis is an autoimmune and inflammatory disease that occurs frequently and is characterized by red, inflamed plaques, and macules, which arise as a result of increased proliferation and poor differentiation of keratin-producing epidermal cells. The writing of article this uses the literature review method. This paper is formed based on information obtained from 15 articles from international journals published in the 2012-2020 period. The references used were obtained by conductingliterature searching from the NCBI database with the keywords psoriasis, dermatology, psoriasis therapy, psoriasis treatment with filters in the form of custom publication ranges for 2012-2020. The result of this literature review is that many drugs have been used for the treatment of psoriasis whose only purpose is to suppress symptoms and improve skin condition. Medications include topical, radiant and systemic, and these therapies are limited and tend to be especially dangerous for long-term use. Advances in the pathogenesis of psoriasis have led to the development of biologically targeted therapies, namely T inhibitor cells (efalizumab and alefacept) and TNF-a inhibitors (etanercept, infliximab and adalimumab). This biological therapy is effective for the treatment of moderate to severe with less side effects than conventional therapy. The use of immunobiological drugs is given parenterally, namely intra-muscular and intra-venous. Psoriasis therapy using biological drugs is recommended to monitor blood chemistry, blood count and CD4, ANA antibodies, tuberculin tests, medical history and physical examination depending on the type of therapy, certain vaccinations are also recommended to prevent infection.